UV-C inactivation of microorganisms in droplets on food contact surfaces using UV-C light-emitting diode devices - Sharma, Aakash; Mahmoud, Housyn; Pendyala, Brahmaiah; Balamurugan, Sampathkumar; Patras, Ankit (Frontiers in Food Science and Technology, 2023)
The main objective of this study was to investigate the effectiveness of ultraviolet light (UV-C) emitting diodes for the decontamination of stainless-steel food contact surfaces. Listeria monocytogenes (ATCC 19115), Escherichia coli (ATCC 25922) and Salmonella enterica serovar Typhimurium (ATCC 700720) were chosen as challenge microorganisms. Target microorganisms were subjected to UV-C dosage of 0, 2, 4, 6 and 8 mJ.cm-2 at an average fluence of 0.163 mW/cm2 using a near collimated beam operating at 279 nm wavelength. Escherichia coli showed lower sensitivity to UV-C light compared to Salmonella Typhimurium and followed first order kinetics. Escherichia coli and Salmonella Typhimurium were reduced by more than 3 log10 cycles at the maximum UV dosage of 12 mJ.cm-2. In contrast, Listeria monocytogenes followed Weibull model with an apparent shoulder in the initial doses. A maximum reduction of 4.4 log10 was achieved at the highest exposure level. This study showed that UV-C LED devices represent an excellent alternative for the inactivation of food-borne micro-organisms in droplets. Results clearly demonstrate that UV-C LED devices can serve as an additional sanitation method to routine cleaning practices which are commonly utilized in the food industry.